A novel two-step process for enhancing adhesion strength of cold-spray metallization of carbon fiber-reinforced plastics - Jiayu Sun; Kenta Yamanaka; Chrystelle Bernard; Yuchao Lei; Shaoyun Zhou; Hao Lin; Kazuhiro Ogawa; Akihiko Chiba (Materials & Design)
Cold-spray processing is a promising technique for the metallization of carbon fiber-reinforced plastics (CFRPs). However, the adhesion between the cold-sprayed metal deposits and CFRP substrate needs to be improved. In this study, a novel two-step strategy was developed to significantly enhance the adhesion strength of cold-sprayed Sn/epoxy-based CFRP interfaces. The first step involved eroding the CFRP substrate at a high gas temperature (623 K) to artificially expose the carbon fibers at the surface. In the second step, Sn particles were deposited on the eroded CFRP substate at 523 K, forming a uniform coating. The exposed carbon fibers (CFs) serve as linkages and anchors at the Sn/CFRP interfaces, significantly enhancing the adhesion strength of the single-step Sn coating (∼2 MPa) to ∼ 6.25 MPa after three or more passes. A surface roughness of Sa ≈ 40 μm after the first step was optimal for enhancing the mechanical interlocking at the interfaces. These findings emphasize the importance of interfacial modification in enhancing the mechanical interlocking between the materials, which is crucial for the dominant adhesion mechanism, and suggest an effective strategy that can be applied in continuous cold-spray processing.